Endoscopic resection outcomes and predictors of failed en bloc endoscopic mucosal resection of colorectal polyps ≤ 20 mm among advanced endoscopy trainees - King, William W.; Draganov, Peter V.; Wang, Andrew Y.; Uppal, Dushant; Rumman, Amir; Kumta, Nikhil A.; DiMaio, Christopher J.; Trindade, Arvind J.; Sejpal, Divyesh V.; D’Souza, Lionel S.; Bucobo, Juan C.; Gomez, Victoria; Wallace, Michael B.; Pohl, Heiko; Yang, Dennis (Endoscopy International Open, 2021)
Background and study aims En bloc endoscopic mucosal resection (EMR) is preferred over piecemeal resection for polyps ≤ 20 mm. Data on colorectal EMR training are limited. We aimed to evaluate the en bloc EMR rate of polyps ≤ 20 mm among advanced endoscopy trainees and to identify predictors of failed en bloc EMR.Methods This was a multicenter prospective study evaluating trainee performance in EMR during advanced endoscopy fellowship. A logistic regression model was used to identify the number of procedures and lesion cut-off size associated with an en bloc EMR rate of ≥ 80 %. Multivariate analysis was performed to identify predictors of failed en bloc EMR.Results Six trainees from six centers performed 189 colorectal EMRs, of which 104 (55 %) were for polyps ≤ 20 mm. Of these, 57.7 % (60/104) were resected en bloc. Trainees with ≥ 30 EMRs (OR 6.80; 95 % CI: 2.80–16.50; P = 0.00001) and lesions ≤ 17 mm (OR 4.56;95 CI:1.23–16.88; P = 0.02) were more likely to be associated with an en bloc EMR rate of ≥ 80 %. Independent predictors of failed en bloc EMR on multivariate analysis included: larger polyp size (OR:6.83;95 % CI:2.55–18.4; P = 0.0001), right colon location (OR:7.15; 95 % CI:1.31–38.9; P = 0.02), increased procedural difficulty (OR 2.99; 95 % CI:1.13–7.91; P = 0.03), and having performed < 30 EMRs (OR: 4.87; 95 %CI: 1.05–22.61; P = 0.04).Conclusions In this pilot study, we demonstrated that a relatively low proportion of trainees achieved en bloc EMR for polyps ≤ 20 mm and identified procedure volume and lesion size thresholds for successful en bloc EMR and independent predictors for failed en bloc resection. These preliminary results support the need for future efforts to define EMR procedure competence thresholds during training.